Analysis on the development trend of EU data protection legislation reform - Min ZHANG; Min-hu MA (网络与信息安全学报)
EU data protection legislation reforming has become the attention by countries in the world.That EU data protection legislation reforming concentrated on promoting the unity of legislation and the consistency and effi-ciency of law enforcement and reinforcing the protection of personal data rights,enhancing EU-US bilateral coop-eration in the protection of personal data,rebuilding the trust mechanism of data flow was stated.That China should focus on the profound influence power by the development trend of EU data protection legislation reform was pro-posed.